Law's Application of The Government to Responding People Smuggling - Usman Mutaqin; Ivan Lukky Pujangga; ZulfaQotrun Nada (Faculty of Law, University of Mataram, 2021)
People smuggling is a transnational crime, that a person illegally crosses international borders from one, or more countries, by secret means, by fraud, or by using forged documents. People Smuggling, putting illegal immigrants and refugees as an opportunity for material gain. The potential for people smuggling in Indonesia is vulnerable, supported by the geographical factor of a vast coastline. As one of the world's trade routes, it must receive serious attention. With this urgency, this study discusses the role of the government in implementing legal policies in cases of people smuggling in Indonesia. This study applied a descriptive method with qualitative analysis. This paper concludes that people smuggling has been criminalized as transnational organized crime and included in the immigration law instruments in Indonesia.